50. CLINICAL, LABORATORIES FEATURES AND TREATMENT OUT OF ENTEROVIRUS MENINGITIS (Vietnam Journal of Community Medicine, 2025)
Objectives: Describe clinical, laboratory characteristics and outcomes of meningitis caused by Enterovirus.Subjects: The study describes 297 children aged 1 month to 15 years diagnosed with meningitis caused by Enterovirus, with molecular biological testing determining the presence of Enterovirus in the cerebrospinal fluid, treated at the Center for Tropical Diseases, National Children’s Hospital from January 1, 2020 to December 31, 2020.Research methods: Retrospective study describing a series of cases.Results: The proportion of boys is higher than that of girls (2.3/1), the most common age group is over 5 years old (73.8%), the number of cases increases in July to October. Symptoms of fever account for 89.6%, vomiting 88.9%, headache 88.9%, stiff neck 64.6%. The number of white blood cells in the cerebrospinal fluid from 10-500 cells accounted for 83.2%, and 9.1% had cells increased over 500 cells. Protein and sugar in the cerebrospinal fluid did not change with average values ​​of 0.44 ± 0.21 g/l and 3.9 ± 0.6 mmol/l, respectively. The rate of complete recovery without sequelae was 100% at the time of discharge with an average treatment time of 5.7 ± 1.9 days.Conclusions: Meningitis caused by Enterovirus is a benign disease, commonly found in children over 5 years old. All children recovered without sequelae.
Keywords: Viral meningitis; Enterovirus meningitis